Estratégias de adaptação e mitigação das emissões de gases do efeito estufa: o caso CAGECE - Perini, Dario Sidrim (2011)
Since the Industrial Revolution the environment has been facing consequences of the intensive usage of natural resources by man. Emissions of greenhouse gases (GHGs) have grown at a much higher amount than the absorption capacity of the planet, which has concerned government, scientists and society, mainly due to projections of impacts resulted from climate changes and global warming, with serious damage to all inhabitants of the planet. This issue also affects enterprises, responsible for most greenhouse gas emissions, and it consequently ends up influencing their strategies. The purpose of this paper is to analyze risks and business opportunities arising from the adoption of an adaptation strategy and mitigation of greenhouse gases. It has been structured through a case study at the Water and Sewage Company from Ceará (CAGECE), a company of basic sanitation, given the importance of this sector to society and considering that, although the climate change problem is at global level, initiatives should be local, otherwise it will not be possible to reverse the scenario projected by scientists of the Intergovernmental Panel on Climate Change (IPCC). The research is characterized as exploratory and qualitative, conducted through the collection of secondary data and semi-structured interviews with managers at CAGECE. The study identifies the regulatory constraints and the recognition of opportunities by the company managers. Through such analysis, it identifies the company's strategic positioning before climate changes. In addition, it evaluates potential projects for reducing GHG emissions and their technical and environmental feasibility. The research reveals that the environment in which CAGECE acts has low pressure from stakeholders for implementing actions to reduce emissions, although legislation is expected to become increasingly stringent. On the other hand, it is noticed that CAGECE managers recognize opportunities in this low carbon market, justifying investments on projects that reduce GHG emissions. According to the proposed classification, CAGECE adopts a strategy that lies between the profile “entrepreneur” and "investor", as there is under pressure from stakeholders, but act proactively in the elaboration of studies and research in potential projects to reduce GHG emissions and generates carbon credits through the Clean Development Mechanism (CDM).